Effect of growth stage on the concentrations of mineral elements and other nutrients in pasture grasses - Sattar, Abdus (1981)
Total ash and concentrations of nutrients such as protein, fat. Na, K, Ca, Mg, Fe, Cu, Zn and Vin in several pasture grasses, grown at a single location were determined at varying growth stages. The study revealed significant differences (l'0.01) in these nutrients among grasses and their different growth stages.